Financial Distress dan Internal Control pada Earnings Management dengan Managerial Ownership Sebagai Moderasi - Cahyaningrum, Nadya; Gunawan, Juniati; Anis, Idrianita (E-Jurnal Akuntansi; Vol 32 No 6 (2022), 2022)
This study aims to examine the effect of financial distress and internal control on earnings management, as well as to examine the role of managerial ownership in moderating financial distress and internal control. This study uses secondary data in the form of annual reports of banks listed on the Indonesia Stock Exchange from 2016-2020 with 145 samples. The analysis used in this study is a panel data analysis model. The results of this study indicate that financial distress has no significant effect on real earnings management, internal control has a negative and significant effect on real earnings management, management ownership doesn’t moderate or weaken the relationship between financial distress and internal control on real earnings management, financial distress, and internal control has no significant effect on accrual earnings management, and the results show that management ownership weakens the relationship between financial distress and internal control on accrual earnings management. Keywords: Financial Distress; Internal Control; Real Earnings Management; Accrual Earnings Management; Management Ownership.